Polymer water-based fire extinguishing material and preparation method thereof
Patent Information
- Application Number
- CN202611297855.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-30
AI Technical Summary
仅依靠含水凝胶维持覆盖,容易因失水收缩产生界面脱离或局部缺陷
[0030]1、经定向官能化的两类水溶性多糖在分装状态下彼此隔离,各自能够保持稳定的流动性,便于储存、泵送和喷射。两组分在喷口处接触后,分布于不同分子链上的互补位点可以在较短的链段移动距离内形成大量连接节点,使分散的多糖链迅速转变为连续网络。该网络不是依靠大幅提高喷射前黏度获得,而是在材料喷出后原位形成,因此既能保证输送过程顺畅,又能使材料到达倾斜面或垂直燃烧面后快速降低流动性,延长水分和二氧化碳释放组分在燃烧区域的停留时间。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of fire protection technology, belonging to patent classification number A62D1 / 00, specifically to a polymer water-based fire extinguishing material and its preparation method. Background Technology
[0002] Water-based fire extinguishing materials utilize the heat absorption and vaporization properties of water to lower the temperature of burning materials, making them suitable for extinguishing fires on solid surfaces and porous materials. However, ordinary water-based materials have high fluidity and tend to flow when sprayed onto inclined, vertical, or high-temperature surfaces, making it difficult to form a stable covering layer. After the moisture gradually evaporates, the surface of the burning material will re-come into contact with air, potentially leading to smoldering or reignition.
[0003] Incorporating a carbon dioxide release system into water-based materials can reduce the oxygen concentration in the combustion zone using carbon dioxide, which works in conjunction with the cooling effect of water. However, if the release components are in direct contact during storage, they are prone to premature reaction, leading to carbon dioxide loss, increased container pressure, and deterioration of material properties. Conversely, if the release process is set too slowly, carbon dioxide may not reach the combustion interface in time. Therefore, the release components need to remain stable during storage and transportation, while also activating rapidly after the material is ejected.
[0004] To minimize material loss, the sprayed water-based material needs to gel rapidly. Insufficient gelation will cause the material to flow away from the surface of the combustor before gel formation; excessive gelation may cause the emerging carbon dioxide bubbles to be prematurely fixed, leaving interconnected channels in the capping layer. Oxygen can then re-enter the surface of the combustor through these channels, making it difficult for the rapidly gelled capping layer to continue its oxygen-barrier function.
[0005] Furthermore, the moisture in the gel continues to migrate and evaporate after fire extinguishing. Relying solely on hydrogels to maintain coverage is prone to interfacial detachment or localized defects due to shrinkage caused by water loss. To achieve a sustained oxygen barrier effect, the cover layer should also form a stable, continuous barrier structure with a long gas diffusion path after the moisture content decreases, while avoiding the barrier structure hindering early gelation and carbon dioxide release.
[0006] Therefore, the technical problem that this invention needs to solve is to enable the material to rapidly gel and release carbon dioxide simultaneously after it is sprayed, while ensuring that each functional component can be stored stably and transported smoothly, and to inhibit the formation of through-holes in the gel during the gas release process, so that the covering layer can remain continuous, adhered and have a low oxygen permeability oxygen barrier structure after the moisture gradually decreases, thereby achieving rapid fire extinguishing, reducing loss and inhibiting reignition. Summary of the Invention
[0007] The purpose of this invention is to provide a polymeric water-based fire extinguishing material and its preparation method, so as to solve the technical problems mentioned in the background art.
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] A method for preparing a polymer water-based fire extinguishing material includes the following steps:
[0010] (1) Sodium periodate was used to selectively oxidize dextran to obtain oxidized dextran containing aldehyde group; adipate dihydrazide was grafted onto carboxymethyl cellulose using the EDC / NHS condensation system to obtain hydrazide-modified carboxymethyl cellulose with terminal hydrazide group retained.
[0011] (2) Dopamine is oxidized and deposited on the surface of sodium-based montmorillonite sheets to form a polydopamine layer, and then tetraethyl orthosilicate is hydrolyzed and condensed to form a discontinuous silicon-oxygen structure on the surface of the polydopamine layer, thus obtaining polydopamine-silicon-oxygen interface-locked montmorillonite.
[0012] (3) Neutral mechanically defibrillated cellulose nanofibers, pullulan polysaccharide and the polydopamine-siloxane interfacial locked montmorillonite were dispersed in water to obtain a pore-closed structure dispersion.
[0013] (4) Dissolve the oxidized dextran in a citric acid-trisodium citrate buffer solution to obtain component A; disperse or dissolve the acylhydrazine-carboxymethyl cellulose, sodium bicarbonate and the pore-closed structure dispersion in water to obtain component B; package component A and component B separately so that they are mixed during use and simultaneously form an acylhydrazone crosslinking network and release carbon dioxide.
[0014] Preferably, the dextran in step (1) has a number-average molecular weight of 50,000 to 100,000, the amount of sodium periodate used is 12 to 18% of the molar number of anhydrous glucose units of dextran, and the oxidation reaction is carried out in the dark at 8 to 12°C for 2 to 4 hours.
[0015] After the oxidation reaction was completed, ethylene glycol was added to terminate the reaction at a molar ratio of ethylene glycol to sodium periodate of 1.03 to 1.10:1. The mixture was washed with an ultrafiltration membrane with a molecular weight cutoff of 10 kDa and dried at a temperature not higher than 40°C to obtain oxidized dextran with an aldehyde content of 1.5 to 1.8 mmol / g.
[0016] Preferably, the degree of substitution of the carboxymethyl cellulose in step (1) is 0.6 to 0.9 and the number-average molecular weight is 90,000 to 150,000;
[0017] The molar ratio of EDC·HCl to carboxyl cellulose carboxyl groups was 0.30–0.45:1, the molar ratio of NHS to EDC·HCl was 0.95–1.05:1, and the molar ratio of adipic acid dihydrazide to EDC·HCl was 4.5–6.0:1. The grafting reaction was carried out at pH 4.8–5.2 and 18–22℃ for 10–14 h, and the hydrazide content of the obtained hydrazide-modified carboxyl cellulose was 0.8–1.0 mmol / g.
[0018] Preferably, step (2) includes: adding 100 parts by weight of sodium montmorillonite to 1800-2200 parts by weight of water to swell for 8-12 hours, shearing at 6000-9000 r / min for 20-30 minutes, and adjusting the Tris concentration of the system to 8-12 mmol / L and the pH to 8.3-8.7.
[0019] Add 5-8% (by weight of sodium montmorillonite) of dopamine hydrochloride and react at 20-28°C for 4-6 hours in the presence of air to obtain polydopamine-coated montmorillonite.
[0020] Preferably, the polydopamine-coated montmorillonite is dispersed in a mixed medium of ethanol and water at a mass ratio of 70:30, 25wt% ammonia water at 4-6% relative to the mass of sodium montmorillonite is added, and tetraethyl orthosilicate at 12-18% relative to the mass of sodium montmorillonite is added, and the mixture is reacted at 25-30°C for 3-5 hours.
[0021] The reaction product was washed until neutral and then dried under vacuum at 40–45 °C to obtain the polydopamine-siloxane interfacial locked montmorillonite.
[0022] Preferably, the neutral mechanically defibrillated cellulose nanofibers in step (3) are cellulose nanofibers that have not been oxidized by TEMPO and have not been sulfated, and their carboxyl content is not higher than 0.05 mmol / g;
[0023] Based on the total mass of the composite water-based fire extinguishing material, the dry basis content of cellulose nanofibers is 0.10-0.25%, and the content of pullulan polysaccharide is 0.25-0.60%.
[0024] Preferably, in step (4), the mass fraction of oxidized dextran in component A is 1.6-2.4%, the molar ratio of citric acid to trisodium citrate dihydrate is 4.2-4.5:1, and the pH of component A is 3.1-3.3.
[0025] The amount of protons that the buffer aqueous solution can provide when its initial pH changes to the final pH after the mixture of component A and component B is 1.01 to 1.03 times the molar amount of sodium bicarbonate in component B.
[0026] Preferably, in step (4), component B includes the following raw materials in the following mass percentages: 1.6-2.4% acylhydrazide carboxymethyl cellulose, 3-5% sodium bicarbonate, 1-2% polydopamine-siloxane interlocked montmorillonite, 0.5-1.0% pullulan polysaccharide, and 0.2-0.4% neutral mechanically defibrillated cellulose nanofibers on a dry basis, with the balance being water.
[0027] Preferably, component A and component B are transported in a 1:1 mass ratio through a dual-channel injection device and mixed outside the nozzle; when a static mixing structure is adopted, the internal residence time of component A and component B after contact does not exceed 0.3 seconds, and the pH of the system after the two are mixed and carbon dioxide is released is 5.0 to 5.4.
[0028] A polymeric water-based fire extinguishing material is prepared by the method described above.
[0029] Compared with the prior art, the beneficial effects of the present invention are:
[0030] 1. The two types of water-soluble polysaccharides, after directional functionalization, are isolated from each other in their dispensed state, maintaining stable flowability for easy storage, pumping, and spraying. Upon contact at the nozzle, complementary sites on different molecular chains can form numerous connecting nodes within a short chain segment movement distance, rapidly transforming the dispersed polysaccharide chains into a continuous network. This network is not obtained by significantly increasing the pre-spray viscosity but rather forms in situ after the material is sprayed. Therefore, it ensures smooth transport while rapidly reducing flowability upon reaching the inclined or vertical combustion surface, extending the residence time of moisture and carbon dioxide release components in the combustion zone.
[0031] 2. Montmorillonite treated with interface interlocking has a large aspect ratio. When the capping layer shrinks due to water loss, the lamellar layers can overlap along the surface of the combustible material, forcing oxygen to bypass multiple layers of lamellar structure to reach the combustion interface. The polydopamine interface layer improves the wetting and bonding between montmorillonite and the polysaccharide continuous phase, reducing the possibility of interfacial voids around the lamellar layers. The discontinuous silica structure provides heat-resistant and shrinkage-resistant inorganic support for the lamellar layers, reducing the re-aggregation or local collapse of the lamellar layers after water loss. The resulting oxygen barrier effect does not entirely depend on the capping layer maintaining a high moisture content. Even as the moisture gradually decreases, the overlapping lamellar structure and the inorganic residual skeleton can continue to extend the oxygen diffusion path.
[0032] 3. The rapidly forming gel network fixes the bubble boundaries before carbon dioxide bubbles are completely expelled. As bubbles continue to grow or merge, once they escape from the capping layer, they easily leave interconnected pores and narrow throats, allowing oxygen to bypass the tortuous path formed by the montmorillonite sheets and directly enter the surface of the combustible material. To address this problem, neutral mechanically defibrillated cellulose nanofibers and pullulan are introduced to construct a "fiber-bridging-continuous pore-sealing" structure. Neutral mechanically defibrillated cellulose nanofibers have a high aspect ratio and flexibility, enabling them to intersect between bubble pore walls and adjacent montmorillonite sheets, forming a fibrous skeleton spanning the pores. This restricts small bubbles from merging into larger bubbles and separates potentially interconnected gas channels into smaller, isolated pores. Using unoxidized, neutral varieties reduces interference from additional charged groups on the main gelation process. Pullulan can dissolve in a continuous aqueous phase and enters small regions such as between fibers, at the edges of lamellar sheets, and in the throats of air bubbles during the early stages of gel formation. As water gradually migrates, pullulan accumulates in these regions and forms a continuous membrane with low oxygen permeability, sealing the tiny gaps that the fibrous framework cannot fill. When cellulose nanofibers are used alone, small gaps may still remain between the fibers; when pullulan is used alone, the continuous membrane is insufficient to span larger pores and is prone to shrinkage at the pore edges after water loss. When both are used together, cellulose nanofibers first provide stable pore wall support and a transpore framework, and pullulan then fills and seals the remaining pores based on this framework, thereby transforming large through-holes into small isolated pores and further closing residual throats. This achieves both initial gas inerting and subsequent continuous oxygen barrier without consuming carbon dioxide release components. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] Example 1
[0035] A method for preparing a polymer water-based fire extinguishing material includes the following steps:
[0036] 20.000 g of dextran with a number average molecular weight of 50,000 was added to 480.000 g of water to prepare a 4.0 wt% solution. 3.430 g of sodium periodate was dissolved in 30.000 g of water and then added to the dextran solution. The amount of sodium periodate used was 13% of the molar number of anhydrous glucose units. The reaction was carried out at 8°C for 2 hours in the dark. 1.025 g of ethylene glycol was added, with a molar ratio of ethylene glycol to sodium periodate of 1.03:1, and stirring was continued for 30 minutes. The solution was then washed with 8 times the volume of water using an ultrafiltration membrane with a molecular weight cutoff of 10 kDa until the potassium iodide-starch test of the filtrate was negative. The filtrate was then freeze-dried at a temperature not exceeding 40°C to obtain oxidized dextran with an aldehyde content of 1.50 mmol / g.
[0037] 20.000 g of sodium carboxymethyl cellulose with a degree of substitution of 0.60 and a number-average molecular weight of 90,000 was added to 1313.330 g of MES buffer (50 mmol / L, pH 4.8) to prepare a 1.5 wt% solution. The amount of carboxyl group was calculated on a dry basis and verified by titration to be 56.938 mmol. 4.366 g of EDC·HCl and 2.490 g of NHS were added, with a molar ratio of EDC·HCl to carboxyl group of 0.40:1 and a molar ratio of NHS to EDC·HCl of 0.95:1, and the mixture was activated for 10 min. 17.854 g of adipic acid dihydrazide was dissolved in 339.226 g of water to prepare a 5.0 wt% solution, adjusted to pH 4.8, and then added; the molar ratio of adipic acid dihydrazide to EDC·HCl was 4.5:1. The reaction was carried out at 18℃ and pH=4.8±0.1 for 10 h, followed by washing with a 10 kDa ultrafiltration membrane for 8 dialysis volumes, and then freeze-drying at a temperature not exceeding 40℃ to obtain acylhydrazide-modified carboxymethyl cellulose with an acylhydrazide content of 0.80 mmol / g.
[0038] 20,000 g of sodium montmorillonite was added to 360,000 g of water and swelled for 8 hours, then sheared at 6000 r / min for 20 minutes. 0.349 g of Tris was added, and the pH was adjusted to 8.3 with 1.0 mol / L hydrochloric acid to achieve a Tris concentration of 8 mmol / L. 1,000 g of dopamine hydrochloride was added, and the mixture was reacted at 20°C for 4 hours in the presence of air. The solid phase was separated and washed three times with water. The equivalent of 20,000 g of dry montmorillonite was taken, and after accounting for the water introduced by the wet material, ethanol and water were added to bring the total mass of the dispersion medium to 240,000 g and the ethanol-to-water mass ratio to 70:30. 0.800 g of 25 wt% ammonia solution was added, and the mixture was stirred for 10 minutes. Then, 2.400 g of tetraethyl orthosilicate was added dropwise over 30 minutes, and the mixture was reacted at 25°C for 3 hours. The product was washed sequentially with 70wt% ethanol aqueous solution and water until neutral, and then dried under vacuum at 40℃ to obtain polydopamine-siloxane interfacial locked montmorillonite.
[0039] Preparation of Component A: 25.430 g of anhydrous citric acid, 8.650 g of trisodium citrate dihydrate, and 8.000 g of the above-mentioned oxidized dextran were dissolved in 457.920 g of water to obtain 500.000 g of Component A. The content of oxidized dextran was 1.6 wt%, the molar ratio of citric acid to trisodium citrate dihydrate was 4.50:1, and the initial pH of Component A was approximately 3.17. From the initial pH to the final mixing pH of 5.0, the buffer system could provide approximately 0.18034 mol of effective protons, which is 1.01 times the amount of sodium bicarbonate in Component B.
[0040] Preparation of Component B: 66.667 g of a neutral mechanically defibrillated cellulose nanofiber dispersion with a solid content of 1.5 wt% was mixed with 402.833 g of water. The cellulose nanofibers were not oxidized by TEMPO or sulfation, and had a carboxyl content of 0.01 mmol / g. 2.500 g of pullulan was added and stirred at 30 °C until completely dissolved. 5.000 g of the modified montmorillonite was added and sheared at 3000 r / min for 10 min. After reducing the rotation speed, 8.000 g of the hydrazide-modified carboxymethyl cellulose was added and hydrated for 60 min. When the temperature was no higher than 30 °C, 15.000 g of sodium bicarbonate was added and stirred until completely dissolved to obtain 500.000 g of Component B.
[0041] The dry basis contents of hydroxymethyl cellulose hydrazide, sodium bicarbonate, modified montmorillonite, pullulan, and cellulose nanofibers in component B are 1.6 wt%, 3.0 wt%, 1.0 wt%, 0.5 wt%, and 0.2 wt%, respectively; based on 1000.00 g of finished product, the contents of cellulose nanofibers and pullulan are 0.10 wt% and 0.25 wt%, respectively.
[0042] Components A and B are stored separately in sealed containers and transported at a 1:1 mass ratio. The internal residence time after contact is controlled at 0.30 seconds, and the final pH of the mixture is controlled at 5.0. When 15,000 g of sodium bicarbonate is completely released, 0.17856 mol of carbon dioxide is generated, which is approximately 4.37 L at 25 °C and 101.3 kPa.
[0043] Example 2
[0044] A method for preparing a polymer water-based fire extinguishing material includes the following steps:
[0045] 20.000 g of dextran with a number average molecular weight of 75,000 was added to 380.000 g of water to prepare a 5.0 wt% solution. 3.958 g of sodium periodate was dissolved in 40.000 g of water and added to the solution; the amount of sodium periodate was 15% of the molar number of anhydrous glucose units. The reaction was carried out at 10 °C for 3 h under light-protected conditions. 1.223 g of ethylene glycol was added, with a molar ratio of ethylene glycol to sodium periodate of 1.065:1, and stirring was continued for 40 min. The solution was washed through a 10 kDa ultrafiltration membrane for 8 dialysis volumes until the potassium iodide-starch test of the filtrate was negative. The solution was then lyophilized at a temperature not exceeding 40 °C to obtain oxidized dextran with an aldehyde content of 1.65 mmol / g.
[0046] Take 20.000 g of sodium carboxymethyl cellulose with a degree of substitution of 0.90 and a number-average molecular weight of 120,000, and add 980.000 g of MES buffer with a concentration of 50 mmol / L and a pH of 5.0 to prepare a 2.0 wt% solution. The amount of carboxyl group is 76.575 mmol. Add 4.404 g of EDC·HCl and 2.644 g of NHS, with a molar ratio of EDC·HCl to carboxyl group of 0.30:1 and a molar ratio of NHS to EDC·HCl of 1.00:1, and activate for 15 min. Dissolve 21.010 g of adipic acid dihydrazide in 399.190 g of water to prepare a 5.0 wt% solution, adjust the pH to 5.0, and then add it; the molar ratio of adipic acid dihydrazide to EDC·HCl is 5.25:1. The reaction was carried out at 20℃ and pH 5.0±0.1 for 12 h, followed by washing with a 10 kDa ultrafiltration membrane for 8 dialysis volumes and lyophilization to obtain hydrazide-modified carboxymethyl cellulose with an acylhydrazine content of 0.90 mmol / g.
[0047] 20,000 g of sodium montmorillonite was added to 400,000 g of water and swelled for 10 h, then sheared at 7500 r / min for 25 min. 0.485 g of Tris was added, and the pH was adjusted to 8.5 with 1.0 mol / L hydrochloric acid to achieve a Tris concentration of 10 mmol / L. 1.300 g of dopamine hydrochloride was added, and the mixture was reacted at 24 °C for 5 h in the presence of air. The mixture was separated and washed three times with water. The equivalent of 20,000 g of dry montmorillonite was taken, and after accounting for the water introduced by the wet mixture, ethanol and water were added to bring the total mass of the dispersion medium to 300,000 g, including 210,000 g of ethanol and 90,000 g of water. 1,000 g of 25 wt% ammonia solution was added, and the mixture was stirred for 10 min. Then, 3,000 g of tetraethyl orthosilicate was added dropwise, and the mixture was reacted at 27.5 °C for 4 h. After washing until neutral, the mixture was vacuum dried at 42.5℃ to obtain polydopamine-siloxane interfacial locked montmorillonite.
[0048] Preparation of Component A: 30.970 g anhydrous citric acid, 10.900 g trisodium citrate dihydrate, and 10.000 g of the above-mentioned oxidized dextran were dissolved in 448.130 g of water to obtain 500.000 g of Component A. The content of oxidized dextran was 2.0 wt%, the molar ratio of citric acid to trisodium citrate dihydrate was approximately 4.35:1, and the initial pH of Component A was approximately 3.20. From the initial pH to the final mixing pH of 5.2, the buffer system could provide approximately 0.24288 mol of effective protons, which is 1.02 times the amount of sodium bicarbonate in Component B.
[0049] Preparation of Component B: 75.000 g of a neutral mechanically defibrillated cellulose nanofiber dispersion with a solid content of 2.0 wt% was mixed with 383.750 g of water. The cellulose nanofibers had a carboxyl content of 0.03 mmol / g. 3.750 g of pullulan was added and stirred at 32 °C until dissolved. 7.500 g of modified montmorillonite was added and sheared at 3000 r / min for 10 min. After reducing the rotation speed, 10.000 g of hydrazide-modified carboxymethyl cellulose was added and hydrated for 60 min. 20.000 g of sodium bicarbonate was added at a temperature not exceeding 30 °C and stirred until dissolved, yielding 500.000 g of Component B.
[0050] The dry basis contents of hydroxymethyl cellulose hydrazide, sodium bicarbonate, modified montmorillonite, pullulan, and cellulose nanofibers in component B are 2.0 wt%, 4.0 wt%, 1.5 wt%, 0.75 wt%, and 0.30 wt%, respectively; based on the finished product, the contents of cellulose nanofibers and pullulan are 0.15 wt% and 0.375 wt%, respectively.
[0051] Components A and B are transported at a 1:1 mass ratio, with a residence time of 0.15 seconds in a short-path static mixer, and the final pH of the mixture is controlled at 5.2. When 20,000 g of sodium bicarbonate is completely released, 0.23808 mol of carbon dioxide is generated, which is approximately 5.82 L at 25 °C and 101.3 kPa.
[0052] Example 3
[0053] A method for preparing a polymer water-based fire extinguishing material includes the following steps:
[0054] 20.000 g of dextran with a number average molecular weight of 100,000 was added to 313.330 g of water to prepare a 6.0 wt% solution. 4.749 g of sodium periodate was dissolved in 50.000 g of water and added to the solution; the amount of sodium periodate used was 18% of the molar number of anhydrous glucose units. The reaction was carried out at 12 °C for 4 h under light-protected conditions. 1.516 g of ethylene glycol was added, with a molar ratio of ethylene glycol to sodium periodate of 1.10:1, and stirring was continued for 45 min. The solution was washed through a 10 kDa ultrafiltration membrane for 8 dialysis volumes until the potassium iodide-starch test of the filtrate was negative. The solution was then lyophilized at a temperature not exceeding 40 °C to obtain oxidized dextran with an aldehyde content of 1.80 mmol / g.
[0055] Take 20.000 g of sodium carboxymethyl cellulose with a degree of substitution of 0.90 and a number-average molecular weight of 150,000, and add 780.000 g of MES buffer with a concentration of 50 mmol / L and a pH of 5.2 to prepare a 2.5 wt% solution. The amount of carboxyl group is 76.575 mmol. Add 6.606 g of EDC·HCl and 4.164 g of NHS, with a molar ratio of EDC·HCl to carboxyl group of 0.45:1 and a molar ratio of NHS to EDC·HCl of 1.05:1, and activate for 20 min. Dissolve 36.016 g of adipic acid dihydrazide in 684.304 g of water to prepare a 5.0 wt% solution, adjust the pH to 5.2, and then add it; the molar ratio of adipic acid dihydrazide to EDC·HCl is 6.0:1. The reaction was carried out at 22℃ and pH=5.2±0.1 for 14 h, followed by washing with a 10 kDa ultrafiltration membrane for 8 dialysis volumes and lyophilization to obtain hydrazide-modified carboxymethyl cellulose with an acylhydrazine content of 1.00 mmol / g.
[0056] 20,000 g of sodium montmorillonite was added to 440,000 g of water and swelled for 12 h, then sheared at 9000 r / min for 30 min. 0.640 g of Tris was added, and the pH was adjusted to 8.7 with 1.0 mol / L hydrochloric acid to achieve a Tris concentration of 12 mmol / L. 1.600 g of dopamine hydrochloride was added, and the mixture was reacted at 28 °C for 6 h in the presence of air. The mixture was separated and washed three times with water. The equivalent of 20,000 g of dry montmorillonite was taken, and after accounting for the water introduced by the wet mixture, ethanol and water were added to bring the total mass of the dispersion medium to 360,000 g, including 252,000 g of ethanol and 108,000 g of water. 1.200 g of 25 wt% ammonia solution was added, and the mixture was stirred for 10 min. Then, 3.600 g of tetraethyl orthosilicate was added dropwise, and the mixture was reacted at 30 °C for 5 h. After washing until neutral, the mixture was vacuum dried at 45°C to obtain polydopamine-siloxane interfacial locked montmorillonite.
[0057] Preparation of Component A: 35.920 g of anhydrous citric acid, 13.090 g of trisodium citrate dihydrate, and 12.000 g of the above-mentioned oxidized dextran were dissolved in 438.990 g of water to obtain 500.000 g of Component A. The content of oxidized dextran was 2.4 wt%, the molar ratio of citric acid to trisodium citrate dihydrate was approximately 4.20:1, and the initial pH of Component A was approximately 3.22. From the initial pH to the final mixing pH of 5.4, the buffer system could provide approximately 0.30662 mol of effective protons, which is 1.03 times the amount of sodium bicarbonate in Component B.
[0058] Preparation of Component B: 80.000 g of a neutral mechanically defibrillated cellulose nanofiber dispersion with a solid content of 2.5 wt% was mixed with 368.000 g of water. The cellulose nanofibers had a carboxyl content of 0.05 mmol / g. 5.000 g of pullulan was added and stirred at 35 °C until completely dissolved. 10.000 g of modified montmorillonite was added and sheared at 3000 r / min for 10 min. After reducing the rotation speed, 12.000 g of hydrazide-modified carboxymethyl cellulose was added and hydrated for 60 min. 25.000 g of sodium bicarbonate was added at a temperature not exceeding 30 °C and stirred until dissolved, yielding 500.000 g of Component B.
[0059] The dry basis contents of hydroxymethyl cellulose hydrazide, sodium bicarbonate, modified montmorillonite, pullulan, and cellulose nanofibers in component B are 2.4 wt%, 5.0 wt%, 2.0 wt%, 1.0 wt%, and 0.4 wt%, respectively; based on the finished product, the contents of cellulose nanofibers and pullulan are 0.20 wt% and 0.50 wt%, respectively.
[0060] Components A and B are delivered at a 1:1 mass ratio through a dual-channel nozzle and mixed outside the nozzle. The internal residence time of the components after contact is controlled at 0.05 seconds, and the final pH of the mixture is controlled at 5.4. When 25,000 g of sodium bicarbonate is completely released, 0.29760 mol of carbon dioxide is generated, which is approximately 7.28 L at 25 °C and 101.3 kPa.
[0061] Comparative Example 1: The 8.000g oxidized dextran in component A of Example 1 was replaced with 8.000g unoxidized dextran. The amounts of other raw materials, preparation conditions, component ratios and usage methods were the same as in Example 1.
[0062] Comparative Example 2: 8.000g of hydrazide-modified carboxymethyl cellulose in component B of Example 1 was replaced with 8.000g of unhydrazide-modified sodium carboxymethyl cellulose. The amounts of other raw materials, preparation conditions, component ratios and usage methods were the same as in Example 1.
[0063] Comparative Example 3: 5.000g of polydopamine-siloxane interlocking montmorillonite in component B of Example 1 was replaced with 5.000g of unmodified sodium-based montmorillonite. The amounts of other raw materials, preparation conditions, component ratios and usage methods were the same as in Example 1.
[0064] Comparative Example 4: Polydopamine-coated montmorillonite of equal dry basis weight was used to replace the polydopamine-siloxane interlocking montmorillonite in Example 1, and the tetraethyl orthosilicate hydrolysis and condensation treatment was omitted. The remaining raw material amounts, preparation conditions, component ratios and usage methods were the same as in Example 1.
[0065] Comparative Example 5: The 66.667g cellulose nanofiber dispersion in component B of Example 1 was omitted, and 66.667g deionized water was added. 2.500g pullulan was retained. The amount of other raw materials, preparation conditions, component ratios and usage methods were the same as in Example 1.
[0066] Comparative Example 6: 2.500g pullulan polysaccharide was omitted from component B of Example 1, and 2.500g deionized water was added. 66.667g cellulose nanofiber dispersion was retained. The amount of other raw materials, preparation conditions, component ratios and usage methods were the same as in Example 1.
[0067] Comparative Example 7: The 66.667g cellulose nanofiber dispersion and 2.500g pullulan polysaccharide in component B of Example 1 were omitted, and 69.167g deionized water was added. The remaining raw material amounts, preparation conditions, component ratios and usage methods were the same as in Example 1.
[0068] Performance testing
[0069] Gelation time test. Following the temperature control and rotation measurement principles of GB / T 10247—2008 "Viscosity Measurement Methods", a rotational rheometer equipped with parallel plates of 25 mm diameter was used. The plate gap was set to 1.00 mm, and the instrument was preheated to 25.0 ± 0.5℃. Component A and component B were delivered by two injection pumps at equal flow rates and directly injected into the spaced parallel plates through a single short-path static mixing head. The timing was initiated at the moment the two components first contacted at the mixing head outlet, and an oscillation time scan was performed at 1.0% strain and 1.0 Hz. The gelation time was defined as the time during which the storage modulus G′ first exceeded the loss modulus G″, and simultaneously G′ reached more than 10 times its initial value, maintaining this state continuously for 10 seconds. The cutoff time for a single test was 300 seconds.
[0070] Vertical surface retention rate test. A 150mm × 300mm Q235 steel test plate was prepared according to GB / T 9271—2008 "Standard Test Plates for Paints and Varnishes", and the evaluation approach for vertical test plates was adopted from GB / T 9264-2012 "Evaluation of Sagging Resistance of Paints and Varnishes". The test plate was placed horizontally, and 45.00g of material was uniformly applied to the plate surface within 8 seconds using a dual-channel metering pump and a disposable static mixing head, corresponding to an application rate of 1.00kg / m². 2 Immediately after application, the test plate is rotated to a vertical position, and the material that flows down or falls off within 30 minutes is collected using a pre-weighed collection tray. The 30-minute retention rate on the vertical surface is calculated as R = (45.00 - m1) / 45.00 × 100%, where m1 is the mass of the material in the collection tray. This method only measures the actual amount of material lost, avoiding the misinterpretation of carbon dioxide escape or small amounts of moisture evaporation as sagging loss.
[0071] 60-second cumulative carbon dioxide release rate test. 50.00g of component A and 50.00g of component B were placed in a 3L sealed reactor equipped with two synchronously invertable inner cups and a mechanical stirrer. The reactor was kept at a constant temperature of 25.0±0.5℃. After an airtightness check, the outlet was connected to a gas measuring device using a carbon dioxide pre-saturated sodium chloride solution as the liquid seal medium. The gas measuring device was zeroed, and the two inner cups were synchronously inverted. Stirring was performed at 300r / min for 10s. The cumulative gas volume within 60s was recorded from the point of contact between the two components, and converted to 25℃ and 101.3kPa. The theoretical carbon dioxide release was calculated using the smaller of the amount of sodium bicarbonate and the effective acid equivalent provided by the acidic component, according to C... 60 =V 60 / V 理论 Calculate the cumulative carbon dioxide release rate over 60 seconds by multiplying by 100%.
[0072] Water retention rate test. After mixing components A and B, let stand for 10 minutes to complete the main gas release process. Accurately weigh 20.00 g of the gelling material and place it in an open-topped petri dish with an inner diameter of 50 mm. Place it in a forced-air drying oven at 60±1℃ for 60 minutes and weigh it. Separately, take samples from the same batch and dry them under vacuum at 60℃ to constant weight to determine the dry matter mass m of the sample. s According to W = (m t -m s ) / (m0-m s The water retention rate is calculated as (m0) × 100%, where m0 is the sample mass before heating, and m... t The sample mass is shown after heating for 60 minutes. The sample container diameter and sample layer thickness are kept constant to reduce errors caused by differences in evaporation area.
[0073] Dry pore structure testing. Components A and B were mixed and immediately injected into a 50mm×50mm×3mm polytetrafluoroethylene mold. After standing for 10 minutes, the mixture was dried to constant weight under vacuum at 40℃, and then equilibrated for 48 hours at 23±2℃ and 50±5% relative humidity. Micron-level X-ray computed tomography was used for scanning, with a voxel size of 5μm. All samples were segmented using the same grayscale threshold, and the volume-weighted equivalent pore size distribution was statistically analyzed. The median pore size of the dried capping layer was characterized by the pore size D50 when the cumulative pore volume reached 50%.
[0074] Oxygen permeability test. Referring to GB / T 19789—2021 "Test Method for Oxygen Permeability of Plastic Films and Sheets for Packaging Materials – Coulometric Test", the mixed material was cast into a film on a polytetrafluoroethylene (PTFE) plate with a limiting frame, dried to constant weight under vacuum at 40℃, and a sample with a dry film thickness of 0.30±0.02 mm was selected and equilibrated for 48 hours at 23±2℃ and 50±5% relative humidity; the effective test area was 50.0 cm². 2 Pure oxygen was used on the oxygen side, and high-purity nitrogen was used on the carrier gas side. The oxygen permeation rate was measured after the permeation state stabilized. All samples were tested using the same dry film thickness, humidification conditions, and effective area. The lower the value, the better the oxygen barrier performance of the dry capping layer.
[0075] Scaled-down timber stack flame extinguishing time test. Following the Class A fire assessment approach of GB 17835—2024 "Water-based Fire Extinguishing Agents", a scaled-down comparative test was conducted in a combustion test chamber equipped with smoke extraction and fire protection facilities. Thirty-six pine strips with a moisture content of 10%–14%, each measuring 20mm × 20mm × 300mm, were stacked in six layers of six strips each, with adjacent layers perpendicular to each other. 100mL of n-heptane was used to ignite the wood stack from below for 120s. After removing the combustion pan, the stack was allowed to burn freely for 60s. Then, components A and B were sprayed from a distance of 1.5m from the stack at a total flow rate of 0.40kg / min. The time from the start of spraying until the visible flame completely disappeared and no further visible flame appeared for 30 seconds was recorded. This test is for quantitative comparison between samples and is not equivalent to the complete type test or fire extinguishing rating determination specified in GB 17835-2024.
[0076] Ignition time test of dry covering layer. Following the cone calorimeter test method in GB / T 16172—2026 "Test Methods for Heat Release Rate and Smoke Production Rate of Building Materials", the material was mixed with component A at a mass ratio of 1:1 to component B, and ignition was performed at 1.00 kg / m³. 2 The application amount was evenly applied to the surface of a 100mm×100mm×20mm pine board; after standing for 10 minutes, it was dried at 60℃ to constant weight, and then equilibrated at 23±2℃ and 50±5% relative humidity for 48 hours; the sample was placed horizontally and heated at 25kW / m2 Tested under conditions of thermal radiation flux and electric spark ignition, the ignition time of the dry-state coating layer was defined as the time during which the sample exhibited and maintained continuous flaming combustion for more than 10 seconds. This indicator is used to evaluate the material's ability to delay re-ignition upon reheating after water loss.
[0077] Table 1:
[0078]
[0079] Note: 300.0* is the cutoff value for the gelation test, indicating that Comparative Example 1 and Comparative Example 2 did not meet the specified gelation criteria within 300s.
[0080] The gelation time in Examples 1-3 was shortened from 8.4 s to 4.7 s, and the vertical surface retention rate and water retention rate increased simultaneously, indicating that as the number of effective connection points in the complementary polysaccharide network increases, the mixed material can transform from a flowable state to a supportive gel more quickly. Comparative Example 1 used unoxidized dextran, and Comparative Example 2 used unacylhydrazide-modified carboxymethyl cellulose. Neither of them met the gelation criterion within 300 s, and the vertical surface retention rates were only 43.1% and 46.8%, respectively. The corresponding flame extinguishing times were extended to 112.4 s and 107.8 s, indicating that the viscosity of the raw materials alone is insufficient to form a stable coating layer on a vertically burning surface.
[0081] Comparative Example 3 used the original sodium-based montmorillonite, with an oxygen permeability of 82.5 cm³ / (m²·24h). Comparative Example 4 retained only the polydopamine coating structure, resulting in an oxygen permeability of 58.3 cm³ / (m²·24h), but still significantly higher than the 31.7 cm³ / (m²·24h) of Example 1. Meanwhile, the gelation times of the three examples were relatively similar, while the ignition times of the dry capping layers were 137.2 s, 175.6 s, and 216.8 s, respectively. This indicates that the interfacial locking structure on the sheet surface mainly improves the dispersion state of the sheets in the polysaccharide continuous phase and the interfacial tightness after drying and shrinkage. Its contribution is mainly reflected in the extension of the oxygen diffusion path and the stability of the dry capping layer, rather than simply by increasing the initial viscosity.
[0082] Neutral mechanically defibrillated cellulose nanofibers and pullulan exhibit a clear functional complementarity. In Comparative Example 6, when only neutral mechanically defibrillated cellulose nanofibers were retained, the elongated nanofibers could form a transpore bridging framework within the gel, limiting the coalescence of carbon dioxide bubbles. Therefore, the dry pore size D50 decreased from 236.7 μm in Comparative Example 7 to 84.2 μm, and the vertical plane retention rate increased from 78.3% to 88.7%. However, small gaps still existed in the nanofiber overlapping areas, and the oxygen permeability remained at 78.8 cm³ / (m²·24h). In Comparative Example 5, when only pullulan was retained, pullulan could form a continuous flexible phase and partially close the pore throats during drying, reducing the oxygen permeability to 64.9 cm³ / (m²·24h). However, due to the lack of spatial support from nanofibers, bubbles still easily coalesced, and the pore size D50 reached 174.5 μm. In Example 1, by using both substances simultaneously, nanofibers first restrict the formation of large bubbles and stabilize the pore walls, while pullulan polysaccharide then fills the tiny gaps at the fiber overlaps and pore throats, further reducing the pore size D50 to 68.4 μm and the oxygen permeability to 31.7 cm³ / (m²·24h). Together, these substances solve the technical problem that after rapid gelation and fixation of carbon dioxide bubbles, the coating layer easily forms interconnected channels during the drying process, leading to oxygen re-entering the surface of the combustible material.
[0083] The cumulative carbon dioxide release rates of all samples over 60 seconds remained at a similar level of 92.8%–99.0%, indicating that the gelling network, layered structure, and nanofiber-pulllan continuous phase did not significantly consume acidic components or sodium bicarbonate. The slightly higher short-term release rates of Comparative Examples 1 and 2 are due to their lack of a rapidly forming network, allowing carbon dioxide to escape more easily; this does not necessarily indicate better overall fire extinguishing performance. The slightly lower short-term release rate of Example 3 is due to the relatively dense network providing short-term confinement to gas escape.
[0084] The flame extinguishing time of Example 2 was 68.9 s, slightly shorter than that of Example 3 (71.3 s). This indicates that while increasing the solid content and network density is beneficial for vertical retention, water retention, and dry oxygen barrier, excessively high viscosity can slightly reduce the efficiency of spray atomization and wetting of wood pores. Example 3 still has the lowest oxygen permeability and the longest dry coating ignition time, making it suitable for emphasizing long-term oxygen barrier performance; Example 2, on the other hand, demonstrates a better overall balance between rapid gelation, spray adaptability, and extinguishing speed.
[0085] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a polymeric water-based fire extinguishing material, characterized in that, Includes the following steps: (1) Sodium periodate was used to selectively oxidize dextran to obtain oxidized dextran containing aldehyde group; adipate dihydrazide was grafted onto carboxymethyl cellulose using the EDC / NHS condensation system to obtain hydrazide-modified carboxymethyl cellulose with terminal hydrazide group retained. (2) Dopamine is oxidized and deposited on the surface of sodium-based montmorillonite sheets to form a polydopamine layer, and then tetraethyl orthosilicate is hydrolyzed and condensed to form a discontinuous silicon-oxygen structure on the surface of the polydopamine layer, thus obtaining polydopamine-silicon-oxygen interface-locked montmorillonite. (3) Neutral mechanically defibrillated cellulose nanofibers, pullulan polysaccharide and the polydopamine-siloxane interfacial locked montmorillonite were dispersed in water to obtain a pore-closed structure dispersion. (4) Dissolve the oxidized dextran in a citric acid-trisodium citrate buffer solution to obtain component A; disperse or dissolve the acylhydrazine-carboxymethyl cellulose, sodium bicarbonate and the pore-closed structure dispersion in water to obtain component B; package component A and component B separately so that they are mixed during use and simultaneously form an acylhydrazone crosslinking network and release carbon dioxide.
2. The preparation method according to claim 1, characterized in that, The number-average molecular weight of the dextran mentioned in step (1) is 50,000 to 100,000, the amount of sodium periodate used is 12 to 18% of the molar number of anhydrous glucose units of dextran, and the oxidation reaction is carried out in the dark at 8 to 12°C for 2 to 4 hours. After the oxidation reaction was completed, ethylene glycol was added to terminate the reaction at a molar ratio of ethylene glycol to sodium periodate of 1.03 to 1.10:
1. The mixture was washed with an ultrafiltration membrane with a molecular weight cutoff of 10 kDa and dried at a temperature not higher than 40°C to obtain oxidized dextran with an aldehyde content of 1.5 to 1.8 mmol / g.
3. The preparation method according to claim 1, characterized in that, The degree of substitution of the carboxymethyl cellulose mentioned in step (1) is 0.6 to 0.9, and the number-average molecular weight is 90,000 to 150,000; The molar ratio of EDC·HCl to carboxyl cellulose carboxyl groups was 0.30–0.45:1, the molar ratio of NHS to EDC·HCl was 0.95–1.05:1, and the molar ratio of adipic acid dihydrazide to EDC·HCl was 4.5–6.0:
1. The grafting reaction was carried out at pH 4.8–5.2 and 18–22℃ for 10–14 h, and the hydrazide content of the obtained hydrazide-modified carboxyl cellulose was 0.8–1.0 mmol / g.
4. The preparation method according to claim 1, characterized in that, Step (2) includes: adding 100 parts by weight of sodium montmorillonite to 1800-2200 parts by weight of water to swell for 8-12 hours, shearing at 6000-9000 r / min for 20-30 minutes, and adjusting the Tris concentration of the system to 8-12 mmol / L and the pH to 8.3-8.
7. Add 5-8% (by weight of sodium montmorillonite) of dopamine hydrochloride and react at 20-28°C for 4-6 hours in the presence of air to obtain polydopamine-coated montmorillonite.
5. The preparation method according to claim 4, characterized in that, The polydopamine-coated montmorillonite was dispersed in a mixed medium of ethanol and water at a mass ratio of 70:30, 25wt% ammonia water (4-6% by mass relative to sodium montmorillonite) was added, and tetraethyl orthosilicate (12-18% by mass relative to sodium montmorillonite) was added. The mixture was reacted at 25-30°C for 3-5 hours. The reaction product was washed until neutral and then dried under vacuum at 40–45 °C to obtain the polydopamine-siloxane interfacial locked montmorillonite.
6. The preparation method according to claim 1, characterized in that, The neutral mechanically defibrillated cellulose nanofibers mentioned in step (3) are cellulose nanofibers that have not been oxidized by TEMPO and have not been sulfated, and their carboxyl content is not higher than 0.05 mmol / g; Based on the total mass of the composite water-based fire extinguishing material, the dry basis content of cellulose nanofibers is 0.10-0.25%, and the content of pullulan polysaccharide is 0.25-0.60%.
7. The preparation method according to claim 1, characterized in that, In step (4), the mass fraction of oxidized dextran in component A is 1.6-2.4%, the molar ratio of citric acid to trisodium citrate dihydrate is 4.2-4.5:1, and the pH of component A is 3.1-3.
3. The amount of protons that the buffer aqueous solution can provide when its initial pH changes to the final pH after the mixture of component A and component B is 1.01 to 1.03 times the molar amount of sodium bicarbonate in component B.
8. The preparation method according to claim 1, characterized in that, In step (4), component B includes the following raw materials in the following mass percentages: 1.6-2.4% acylhydrazide carboxymethyl cellulose, 3-5% sodium bicarbonate, 1-2% polydopamine-siloxane interlocked montmorillonite, 0.5-1.0% pullulan polysaccharide, and 0.2-0.4% neutral mechanically defibrillated cellulose nanofibers on a dry basis, with the balance being water.
9. The preparation method according to claim 1, characterized in that, Component A and component B are delivered in a 1:1 mass ratio through a dual-channel injection device and mixed outside the nozzle; When using a static mixing structure, the internal residence time of component A and component B after contact does not exceed 0.3 seconds, and the pH of the system after the two are mixed and carbon dioxide is released is 5.0 to 5.
4.
10. A polymeric water-based fire extinguishing material, characterized in that, It is prepared by the method described in any one of claims 1 to 9 above.
